AGRARIAN LAND POLICY ON LAND IN INDONESIA POST REGIONAL AUTONOMY - Bintang Ulya Kharisma; Pryo Sularso; Bintara Sura Priambada; Asri Agustiwi; Siti Wulandari (Universitas Muhammadiyah Mataram, 2020)
This study aims to discuss the agrarian law policy in the land sector in Indonesia after regional autonomy. The method used in this research is a normative juridical approach by examining and interpreting theoretical matters regarding the principles, conceptions, doctrines, and legal norms related to land law after post regional autonomy. The research specifications in this research are descriptive analytic using secondary data, including primary legal materials consisting of statutory regulations, official records or minutes of the formation of laws and regulations relating to the issues discussed, and secondary legal materials including books, legal journals., and papers. This study result is that agrarian land policies began in the reform era during the reign of President BJ Habibie, who issued Presidential Decree No. 48/1999 concerning the Policy and Regulatory Study Team in the context Landreform implementation. This policy applies simultaneously with the initiation of regional autonomy. The existence of agrarian reform, especially in the land sector, aims to be advanced, just and independent. The transformation of agrarian reform lies in the arrangement of agrarian resources in an effort to eliminate gaps in land tenure rights and change the pattern of agricultural life to be more productive and sustainable.Keywords: agrarian law; land; post regional autonomy.Penelitian ini bertujuan untuk membahas kebijakan hukum agraria di sektor pertanahan di Indonesia setelah otonomi daerah. Metode yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif dengan memeriksa dan menafsirkan hal-hal teoritis mengenai prinsip, konsepsi, doktrin, dan norma hukum terkait hukum pertanahan setelah pasca otonomi daerah. Spesifikasi penelitian dalam penelitian ini adalah analitik deskriptif menggunakan data sekunder, termasuk materi hukum primer yang terdiri dari peraturan perundang-undangan, catatan resmi atau risalah pembentukan peraturan perundang-undangan yang berkaitan dengan masalah yang dibahas, dan materi hukum sekunder termasuk buku, jurnal hukum, dan makalah. Hasil kajian ini adalah kebijakan lahan agraria dimulai pada era reforma pada masa pemerintahan Presiden BJ Habibie, yang menerbitkan Keputusan Presiden Nomor 48 Tahun 1999 tentang Tim Kajian Kebijakan dan Regulasi dalam rangka implementasi Landreform. Kebijakan ini berlaku bersamaan dengan inisiasi otonomi daerah. Adanya reforma agraria, khususnya di sektor pertanahan, bertujuan untuk maju, berkilasi dan mandiri. Transformasi reforma agraria terletak pada penataan sumber daya agraria dalam upaya menghilangkan kesenjangan hak penguasaan lahan dan mengubah pola kehidupan pertanian menjadi lebih produktif dan berkelanjutan.Kata kunci: hukum agraria; daratan; pasca otonomi daerah.